Partisipasi Masyarakat dalam Mewujudkan Surabaya Kota Layak Anak melalui Program Kampunge Arek Suroboyo Ramah Perempuan dan Anak di RW 05 Balongsari Surabaya - Fadilla, Imro’atul; Supriyanto, Natasya Firdaus; Masithoh, Insani Alfinur; Nursyamsiyah, Silmi Savira; Prathama, Ananta (VISA: Journal of Vision and Ideas, 2024)
The problems of women and children, as well as family problems are one of the problems that occur a lot in society. One of the efforts made by the Surabaya City Government is by implementing the Children's Rightful City Program (KLA) through the Arek Suroboyo Women and Child Friendly Village Program (KAS-RPA). This research aims to analyze community participation in the KAS RPA program in RW 05 Balongsari Village. The research method used is qualitative descriptive with data collection techniques through observation and interviews with the research subject of the Chairman of RW 05, the Great Surabaya Cadre (KSH), and the community of RW 05. The theory used is the participation theory according to Solekhan) which has 4 types, namely participation in decision making, participation in implementation, participation in receiving benefits, and participation in evaluation. The results of the research show that the RW 05 community plays an active role in the implementation of the KAS-RPA program where every stakeholder is involved to work together.